A note on the area of event horizon of Kleinian black hole - Tuan Q. Do (European Physical Journal C: Particles and Fields)
Abstract We point out that the area of event horizon of Kleinian black hole is infinite due to the fact that its event horizon is not a sphere but a hyperboloid. Therefore, the usual interpretations of Schwarzschild black hole might not be applicable to the Kleinian black hole.